2020
DOI: 10.3389/fpls.2020.572703
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Plastid Genomics of Non-Photosynthetic Chrysophytes: Genome Reduction and Compaction

Abstract: Spumella-like heterotrophic chrysophytes are important eukaryotic microorganisms that feed on bacteria in aquatic and soil environments. They are characterized by their lack of pigmentation, naked cell surface, and extremely small size. Although Spumella-like chrysophytes have lost their photosynthetic ability, they still possess a leucoplast and retain a plastid genome. We have sequenced the plastid genomes of three nonphotosynthetic chrysophytes, Spumella sp. Baeckdong012018B8, Pedospumella sp. Jangsampo1202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
3
10
0
Order By: Relevance
“…To this end we constructed a supermatrix of 30 plastid genome-encoded proteins, sampling selected ochrophytes (to have represented all classes with plastid genome data available) and several non-ochrophyte algae as an outgroups. Analyses of the data (6,627 aligned amino acid positions) using the maximum likelihood method and the complex model LG+C60+F+G yielded a tree topology (figure 5) that is generally congruent with recent phylogenetic analyses based on multiple plastid genome-encoded proteins (Ševčíková et al 2019;Han et al 2019;Kim et al 2020;Barcytė et al 2021;Di Franco et al 2022). However, thanks to new plastid genome data that became available only recently, our tree is more comprehensive in terms of the main lineages of ochrophytes represented, and exhibits several notable features.…”
Section: Plastid Genes In Leukarachnion Salinum Are Extremely Divergentsupporting
confidence: 79%
See 1 more Smart Citation
“…To this end we constructed a supermatrix of 30 plastid genome-encoded proteins, sampling selected ochrophytes (to have represented all classes with plastid genome data available) and several non-ochrophyte algae as an outgroups. Analyses of the data (6,627 aligned amino acid positions) using the maximum likelihood method and the complex model LG+C60+F+G yielded a tree topology (figure 5) that is generally congruent with recent phylogenetic analyses based on multiple plastid genome-encoded proteins (Ševčíková et al 2019;Han et al 2019;Kim et al 2020;Barcytė et al 2021;Di Franco et al 2022). However, thanks to new plastid genome data that became available only recently, our tree is more comprehensive in terms of the main lineages of ochrophytes represented, and exhibits several notable features.…”
Section: Plastid Genes In Leukarachnion Salinum Are Extremely Divergentsupporting
confidence: 79%
“…The L. salinum also apparently lacks ferredoxin-NADP + reductase and ferredoxin, the latter being a functionally versatile protein with a redox-active iron-sulfur (Fe-S) cluster and involved in multiple plastid-localized processes beyond photosynthesis itself (Hanke and Mulo 2013). This is even more notable considering the fact that a ferredoxin-encoding gene ( petF ) has been retained by plastid genomes of several independently evolved non-photosynthetic chrysophytes (Dorrell et al 2019; Kim et al 2020). Related to this is the absence in L. salinum of all components of the SUF system, a plastid-specific machinery for the assembly of Fe-S clusters.…”
Section: Resultsmentioning
confidence: 99%
“…However, the recently described genera Poteriospumella and Cornospumella do not show clear ultrastructural evidence, with the leucoplast not appearing to be encircled by the nuclear outer membrane ( Grossmann et al, 2016 ). According to genomic and transcriptomic studies ( Beisser et al, 2017 ; Graupner et al, 2018 ; Olefeld et al, 2018 ; Dorrell et al, 2019 ; Kim et al, 2020 ), the leucoplast of non-photosynthetic Chrysophyceae was found to have a reduced plastid genome. The plastid genome and transcriptome data showed that the non-photosynthetic lineages of chrysophytes lost most of their photosynthesis-related genes and evolved from phototrophic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Spumella- like flagellates are non-photosynthetic unicellular organisms with two unequal flagella that have a simple morphology, e.g., spherical or naked cells ( Cienkowsky, 1870 ; Berglund et al, 2005 ; Boenigk et al, 2005 ; Lepère et al, 2006 ; Charvet et al, 2012 ). They are representative heterotrophic chrysophytes that underwent independent loss of photosynthetic ability in the chrysophyte lineage ( Boenigk et al, 2005 ; Boenigk, 2008 ; Grossmann et al, 2016 ; Kim et al, 2020 ). As they are one of the major bacterivore groups in aquatic systems, their significance in carbon transfer from the microbial loop has been emphasized ( Wylie and Currie, 1991 ; Sanders et al, 1994 ; Sherr and Sherr, 1994 ; Arndt et al, 2000 ; Boenigk and Arndt, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation